hola me pueden ayudar
![](https://es-static.z-dn.net/files/dd0/a77d541e44fa70c80f9846616c770008.jpg)
Respuestas a la pregunta
a) a=1 b=2 c=-8
x= (-2+- raiz cuadrada(2^2-4(1)(-8)))/2(1)
x=(-2+-raiz cuadrada(4+32))/2
x=(-2+-raiz cuadrada(36))/2
x=(-2+-(6))/2
x1=(2+6)/2 x2=(2-6)/2
x1=8/2 x2=-4/2
x1=4 x2=-2
b) a=3 b=-2 c=-1
x= (2+- raiz cuadrada((-2)^2-4(3)(-1)))/2(3)
x=(2+-raiz cuadrada(4+12))/6
x=(2+-raiz cuadrada(16))/6
x=(-2+-(4))/6
x1=(2+4)/2 x2=(2-4)/2
x1=6/2 x2=-2/2
x1=3 x2=-1
c) a=6 b=-5 c=1
x= (5+- raiz cuadrada((-5)^2-4(6)(1)))/2(6)
x=(5+-raiz cuadrada(25-24))/12
x=(5+-raiz cuadrada(1))/12
x=(5+-(1))/12
x1=(5+1)/12 x2=(5-1)/12
x1=6/12 x2=4/12
x1=1/2 x2=1/3
d) a=1 b=-3 c=-10
x= (3+- raiz cuadrada((-3)^2-4(1)(-10)))/2(1)
x=(3+-raiz cuadrada(9+40))/2
x=(3+-raiz cuadrada(49))/2
x=(3+-(7))/2
x1=(3+7)/2 x2=(3-7)/2
x1=10/2 x2=-4/2
x1=5 x2=-2
e) a=1 b=-2 c=-3
x= (2+- raiz cuadrada((-2)^2-4(1)(-3)))/2(1)
x=(2+-raiz cuadrada(4+12))/2
x=(2+-raiz cuadrada(16))/2
x=(2+-(4))/2
x1=(2+4)/2 x2=(2-4)/2
x1=6/2 x2=-2/2
x1=3 x2=-1
f) a=2 b=5 c=-3
x= (-5+- raiz cuadrada(5^2-4(2)(-3)))/2(2)
x=(-5+-raiz cuadrada(25+24))/4
x=(-5+-raiz cuadrada(49))/4
x=(-5+-(7))/4
x1=(-5+7)/4 x2=(-5-7)/4
x1=2/4 x2=-12/4
x1=1/2 x2=-3